2005
DOI: 10.1523/jneurosci.4054-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin in the Rostral Ventromedial Medulla Mediates Opioid-Induced Hyperalgesia and Antinociceptive Tolerance

Abstract: Opioid-induced hyperalgesia is characterized by hypersensitivity to innocuous or noxious stimuli during sustained opiate administration. Microinjection of lidocaine into the rostral ventromedial medulla (RVM), or dorsolateral funiculus (DLF) lesion, abolishes opioidinduced hyperalgesia, suggesting the importance of descending pain facilitation mechanisms. Here, we investigate the possibility that cholecystokinin (CCK), a pronociceptive peptide, may drive such descending facilitation from the RVM during continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(136 citation statements)
references
References 52 publications
5
128
1
2
Order By: Relevance
“…This suggests that pronociceptive systems other than NMDA receptor systems are involved in the long-term expression of SIH. Anti-opioid peptides, such as dynorphin, cholecystokinin, and neuropeptide FF might be good candidates because they have been reported to be involved in opioidinduced hyperalgesia (Vanderah et al, 2000;Xie et al, 2005;Simonin et al, 2006). Studies are in progress to evaluate the role of such endogenous anti-opioid systems in the development of pain vulnerability observed in rats following pain and opioid experiences as reported in this study.…”
Section: Discussionmentioning
confidence: 89%
“…This suggests that pronociceptive systems other than NMDA receptor systems are involved in the long-term expression of SIH. Anti-opioid peptides, such as dynorphin, cholecystokinin, and neuropeptide FF might be good candidates because they have been reported to be involved in opioidinduced hyperalgesia (Vanderah et al, 2000;Xie et al, 2005;Simonin et al, 2006). Studies are in progress to evaluate the role of such endogenous anti-opioid systems in the development of pain vulnerability observed in rats following pain and opioid experiences as reported in this study.…”
Section: Discussionmentioning
confidence: 89%
“…The RVM, which includes the nucleus raphe magnus and the medullary reticular formation, has been identified as a critical region with respect to nociceptive processing and control (31,32). Recently Xie et al (33) reported that CCK in the RVM engages in descending pain facilitatory pathways to enhance spinal nociceptive transmission and attenuate opioid antinociception. Thus, we cannot rule out the possibility that the descending projections from RVM to the spinal cord as well as the interneurons in the spinal dorsal horn might be the origin of CCK in the dorsal horn.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological parameters presented in Table 1 were calculated using the using the pharmacological statistics software FlashCalc version 4.3.2 (Dr. Michael Ossipov, University of Arizona, Tucson, AZ) (Wells et al, 2001;Xie et al, 2005), which is based on the methods described by Tallarida and Murray (1987) and Tallarida (2000). A minimum of three doses was used for each drug.…”
Section: Methodsmentioning
confidence: 99%